Detection of volatile organic compounds in the headspace above mold fungi by GC‐soft X‐radiation–based APCI‐MS. (15th August 2018) - Erler, A.; Riebe, D.; Beitz, T.; Löhmannsröben, H.‐G.; Grothusheitkamp, D.; Kunz, T.; Methner, F.‐J.
Abstract: Mold fungi on malting barley grains cause major economic loss in malting and brewery facilities. Possible proxies for their detection are volatile and semivolatile metabolites. Among those substances, characteristic marker compounds have to be identified for a confident detection of mold fungi in varying surroundings. The analytical determination is usually performed through passive sampling with solid phase microextraction, gas chromatographic separation, and detection by electron ionization mass spectrometry (EI‐MS), which often does not allow a confident determination due to the absence of molecular ions. An alternative is GC‐APCI‐MS, generally, allowing the determination of protonated molecular ions. Commercial atmospheric pressure chemical ionization (APCI) sources are based on corona discharges, which are often unspecific due to the occurrence of several side reactions and produce complex product ion spectra. To overcome this issue, an APCI source based on soft X‐radiation is used here. This source facilitates a more specific ionization by proton transfer reactions only. In the first part, the APCI source is characterized with representative volatile fungus metabolites. Depending on the proton affinity of the metabolites, the limits of detection are up to 2 orders of magnitude below those of EI‐MS. In the second part, the volatile metabolites of the mold fungus species Aspergillus, Alternaria, Fusarium, and Penicillium are investigated. In total, 86 compounds were found with GC‐EI/APCI‐MS. The metabolites identified belong to the substance classes of alcohols, aldehydes, ketones, carboxylic acids, esters, substituted aromatic compounds, terpenes, and sesquiterpenes. In addition to substances unspecific for the individual fungus species, characteristic patterns of metabolites, allowing their confident discrimination, were found for each of the 4 fungus species. Sixty‐seven of the 86 metabolites are detected by X‐ray–based APCI‐MS alone. The discrimination of the fungus species based on these metabolites alone was possible. Therefore, APCI‐MS in combination with collision induced dissociation alone could be used as a supervision method for the detection of mold fungi.